Estudio de la ductilidad en caliente de aceros Fe-Mn-C-Si-Al de plasticidad inducida por Maclaje (TWIP) - Salas Reyes, Antonio Enrique (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The present work mainly studies the single Ti, Ti/B, V, Nb and Mo microalloyed elements over the hot ductility in experimental high-Mn TWIP steel having the basic chemical composition Fe-20Mn-0.45C- 1.5Si-1.5Al which were solidified under two different conditions, the first one using a metallic ingot mold material and the second one using sand ingot mold material. For this purpose, cylindrical specimens were machined and subject to uniaxial hot tensile tests at five temperatures (700, 800, 900, 1000, 1100 °C) under a constant true strain rate of 10-1 s-1. In this sense, hot ductility was quantified as the percentage of reduction of transversal area (%RA) of samples strained to fracture. In a temp to identify the phenomena and those mechanisms related with the hot ductility behavior of studied TWIP steels, carrying out metallographic characterization through light optical microscopy (LOM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and electro backscatter diffraction (EBSD). The obtained results show the benefits of using microalloying elements in TWIP steel. As the testing temperature diminishes the peak stress (σp), since an increase in the resistance is manifested due to a solid solution and precipitation straightening effects. So, in conjunction it was corroborated the formation of second-phase particles by the thermodynamic analysis using FactSage® in a wide range of temperature (600-1600 °C). Results show an improvement at intermediate temperature range (800-900 °C), moderate hot ductility at the lowest testing temperature (700 °C), and a decrease in hot ductility at the higher testing temperature (1100 °C).

En el presente estudio de investigación se estudia el efecto de la adición por separado de los elementos microaleantes tales como el Ti, Ti/B, V, Nb y Mo sobre el comportamiento de ductilidad en caliente de un acero TWIP experimental de composición química base Fe-20Mn-0.45C-1.5Si-1.5Al, solidificados bajo dos condiciones, una rápida utilizando un molde metálico y otra lenta usando un molde de arena sílica. Para ello, se maquinaron probetas de tracción de acero TWIP en la condición de solidificación y se ensayaron uniaxialmente a cinco temperaturas (700, 800, 900, 1000 y 1100 °C) empleando una velocidad de deformación de 10-3 s-1. Así, el porcentaje de reducción de área transversal (%RA) de los especímenes llevados hasta la fractura, se tomó como medida de la ductilidad en caliente. Con la finalidad de identificar los fenómenos y mecanismos involucrados en el comportamiento de la ductilidad en caliente de los diferentes aceros TWIP estudiados, se llevó a cabo la caracterización metalográfica por microscopía óptica, electrónica de barrido y de transmisión, además de emplear la técnica de difracción de electrones retrodispersados (EBSD). Los resultados obtenidos muestran el efecto benéfico de microalear el acero TWIP en términos del esfuerzo pico (σp) ya que en general, se manifiesta un incremento de la resistencia debido a un efecto endurecedor por solución sólida y de endurecimiento por precipitación, donde el estudio termodinámico realizado en FactSage® predijo satisfactoriamente la formación de partículas de segundas fases precipitadas en un amplio rango de temperaturas (600-1600 °C).
Instituto de Investigaciones Metalúrgicas. Doctorado en Ciencias en Metalurgia y Ciencias de los Materiales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1299; info:eu-repo/classification/cti/7; IIM-D-2014-2101; Ductibilidad; Plasticidad; Maclaje